Can Radiologic Tumor Size Following Neoadjuvant Therapy Reliably Guide Tissue Resection in Breast Conserving Surgery in Patients with Invasive Breast Cancer?. Issue 10 (5th December 2020) - Walcott-Sapp, Sarah; Srour, Marissa K.; Lee, Minna; Luu, Michael; Amersi, Farin; Giuliano, Armando; Chung, Alice
Optimum tissue resection volume for patients with invasive breast cancer undergoing breast conserving surgery following neoadjuvant therapy (NAT) is not known. We compared positive margin and in-breast tumor recurrence (IBTR) between 2 groups that were created based on radiologic tumor size (RTS (cm 3 )) at diagnosis, RTS post-NAT, and volume of tissue resected (VTL): Pre-NAT group, patients with VTL closer to RTS at diagnosis, and post-NAT group, patients with VTL closer to post-NAT RTS. 82 patients with 84 breast cancers treated with NAT between 2007 and 2017 who had pre- and post-NAT imaging were identified from a prospectively maintained database. RTS at diagnosis, RTS post-NAT, and VTL were determined. Clinical and treatment characteristics, IBTR, and disease-free survival (DFS) were compared between pre-NAT (n = 51) and post-NAT (n = 33) groups. Compared to post-NAT patients, pre-NAT patients had smaller RTS at presentation (9.2 vs. 33.5 cm 3, P < .001) and post-NAT (1.2 vs. 8.2 cm 3, P = .024). At median follow-up of 4 years, there were no differences between groups in pathologic tumor size, positive margin rate, adjuvant therapy, IBTR, or DFS. Resection volumes that matched RTS on post-NAT imaging were not associated with increased positive margins or IBTR. It may be appropriate to use post-NAT imaging to guide lumpectomy volume.